2020
DOI: 10.13168/agg.2020.0009
|View full text |Cite
|
Sign up to set email alerts
|

Displacement field around an uplifting innovated plate anchor

Abstract: This paper introduces an innovated plate anchor, increasing its bearing section area during uplift. In this experimental study, the influences of embedment depth of plate anchor and soil surface condition (restricted or free) on sand deformation field during uplift test are investigated. In order to study the soil deformation around the anchor, Particle Image Velocimetry (PIV) is used. The experimental setup consists of a camera, a new designed box, load cell, encoder and computer. During the uplift test on ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…ey established the continuous uplift deformation mechanism of soil around the anchor under different mono-bearing capacity ratios. Sabermahani and Nasirabadi [20] used particle image velocimetry (PIV) technology to found that the pullout ability and sand deformation of a bolt are greatly affected by the burial depth. Kumar and Rahaman [21] concluded that the vertical pullout resistance of water plate anchors in sand decreased with an increase in the eccentricity and vertical incline angle.…”
Section: Introductionmentioning
confidence: 99%
“…ey established the continuous uplift deformation mechanism of soil around the anchor under different mono-bearing capacity ratios. Sabermahani and Nasirabadi [20] used particle image velocimetry (PIV) technology to found that the pullout ability and sand deformation of a bolt are greatly affected by the burial depth. Kumar and Rahaman [21] concluded that the vertical pullout resistance of water plate anchors in sand decreased with an increase in the eccentricity and vertical incline angle.…”
Section: Introductionmentioning
confidence: 99%